4D full-vector radio frequency complex magnetic susceptibility mapping. Near-field imaging of RFID tags - Stamenov, Plamen; Ackland, Karl (My University, 2019)
Radio frequency identification (RFID) is a technology permeating both everyday life and scientific applications alike. The most prolific passive tag-based system uses inductively-powered tags with no internal power source [V. Chawla and D. S. Ha, “An overview of passive RFID,” IEEE Commun. Mag. 45(9), 11–17 (2007)]. Here we demonstrate an inductive magnetic field mapping platform on the example of passive near-field RFID tags (ID-1), operating at 13.56 MHz (HF) [Identification cards - Contactless integrated circuit(s) cards - Proximity cards - Part 1: Physical characteristics, ISO/IEC 14443-1, 2000; Part 2: Radio frequency power and signal interface, ISO/IEC 14443-2, 2010; Part 3: Initialization and anticollision, ISO/IEC 14443-3, 2011; Part 4: Transmission protocol, ISO/IEC 14443-4, 2008]. With smaller modules currently being integrated in wrist-bands, watches and items of jewelry, a possible counter-measure to the reduced size is the use of flux-concentrating magnetic material - low-permeability insulating ferrites or high-permeability metallic μ-particle systems such as sendust. Sendust is a magnetically soft iron-rich alloy of Fe, Al and Si - a higher permeability cheaper alternative to permalloy. The integration of sendust components in RFID tags creates a non-trivial multiple-parameter optimization problem, which requires a quantitative RF field imaging system to be used. The RF susceptibility mapping system is comprised of a stepper-motor-driven 4-axial table, which holds the device under test (DUT) or the RFID tag assembly, a source coil (2 turns of 0.5 mm diameter wire, of overall diameter of 21 cm), a 4-micro-coil assembly, allowing for the measurement of Hx, Hy, Hz and dHz/dz, and a 4-channel Vector Network Analyzer (VNA). Four complex transmission spectra are obtained for each spatial point of a rectangular (x, y) grid, and then repeated for a different z-cut. 4D Complex Vector field maps are thus obtained. Simultaneous fitting of the real and imaginary parts of the frequency spectra is possible, at essentially any point of space, to a model comprised of two damped harmonic oscillators. This type of 3D-spatial, full-vector, complex magnetic susceptibility imaging opens ways to the integration of magnetic materials in near-field systems, and is not limited to RFID.
PUBLISHED
cited By 0
Keywords: RFID; Magentic susceptibility; Ferromagnetic materials; Optimization problems; Vector network analyzer; Radiofrequency integrated circuits; Vector fields; Magnetic fields; Radio frequency identification